2014
DOI: 10.1155/2014/572754
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Probiotics, Prebiotics, and Synbiotics on Hypercholesterolemia: A Review

Abstract: Cholesterol plays a major role in human health. High cholesterol is a leading risk factor for human cardiovascular disease such as atherosclerosis, coronary heart disease, and stroke. Excess cholesterol in the bloodstream can form plaque in the artery walls. Hypercholesterolemia is a major risk factor for the development of atherosclerosis. A number of pharmacological and non-pharmacological (including dietary) approaches being employed to reduce the cholesterol level. Numerous drugs that lower serum cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 42 publications
1
48
0
3
Order By: Relevance
“…Since the volunteers were not allowed to consume any probiotics during the intervention, it might lead to IgA reduction. IgA production is affected by the presence of probiotics bacteria (Anandharaj et al 2014). In our findings, milk supplementation could increase probiotic bacteria and led to IgA production, which might explain that IgA concentration on day 9, as the baseline was pretty high and close to IgA concentration after tempeh intervention.…”
supporting
confidence: 56%
“…Since the volunteers were not allowed to consume any probiotics during the intervention, it might lead to IgA reduction. IgA production is affected by the presence of probiotics bacteria (Anandharaj et al 2014). In our findings, milk supplementation could increase probiotic bacteria and led to IgA production, which might explain that IgA concentration on day 9, as the baseline was pretty high and close to IgA concentration after tempeh intervention.…”
supporting
confidence: 56%
“…Probiotic is mainly lactic acid creating bacilli, mostly Lactobacilli [53]. Probiotic may play a beneficial role in several health conditions and performance, including Intestinal microbial composition, therapeutic effects, metabolic effects and immunomodulation [43] [54] [55]. The overall performance and well-being benefits of probiotic microorganisms are repre-sented in Figure 1.…”
Section: Probioticmentioning
confidence: 99%
“…Another fermented dairy product is kefir. But among these, the dominant food vehicles for probiotics are still yogurts and fermented milks, both of which provide a relatively low pH environment in which the probiotic bacteria must survive (Anandharaj et al 2014).…”
Section: Sources Of Probioticsmentioning
confidence: 99%
“…However, many studies have shown that probiotic strains are also found in nondairy fermented substrates which includes soy based products, cereals, legumes, cabbage, maize, pearl millet, sorghum, and so forth (Kechagia et al 2013;Anandharaj et al 2014). …”
Section: Sources Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation